IIUM at 30: some reflections on Islamisation programmes - Md. Noon, Hazizan (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
This paper presents some reflections on IIUM's Islamisation efforts as it travelled through its historical path until today. This modest effort provides a brief account on the University's Islamisation activities and achievements. It highlights some relevant happenings in the course of that history in order to appreciate the dynamics and interplay between permanence and change with regard to this mission,particularly as it relates to the experiences of the University's Faculty of Islamic Revealed Knowledge and Human Sciences (KIRKHS)